A South African perspective on the existence of an interest tax shield - A. J. Pienaar (South African Journal of Economic and Management Sciences, 2000)
This paper investigates whether the use of debt in the capital structure of a company is beneficial to its shareholders. It finds that, in the South African context, gearing has no effect on the value of a company. The use of debt can increase the value of a company in a country where capital profits and interest are taxed equally. This is the result of an interest tax shield, which is directly related to the tax deductibility of interest paid. However, when capital growth and dividends are exempt in the bands of investors, as is the case in South Africa, the interest tax shield does not exist, and there appears to be no benefit in increasing debt.